Pre-Marital Counseling as Preparation for Emotional and Spiritual Readiness for Students of Subulussalam Islamic Boarding School, Plosokandang Village, Kedungwaru District, Tulungagung Regency - Ahmadi Abdul Shomad Faiz Nahdhiyanto; Luqman Fauzi; Ahmad Hanif Fajrin (Journal of Islamic Economy and Community Engagement, 2025)
Marriage is a sacred institution that requires emotional and spiritual readiness for individuals who are about to enter family life. Santri, as the younger generation in the pesantren environment, generally possess normative knowledge of fiqh munakahat (Islamic marital jurisprudence), yet often lack adequate psychological and spiritual preparedness. This community service activity aimed to enhance the emotional and spiritual readiness of santri at Subulussalam Islamic Boarding School through premarital counseling based on a developmental approach.The program was implemented through needs assessment, interactive counseling sessions, communication skills training, conflict resolution simulations, and spiritual values mentoring. The results of the activity indicate a significant improvement in the santri’s knowledge, attitudes, and skills related to marital dynamics. The santri gained a better understanding of the importance of emotional regulation, spousal communication, family responsibility, and the spiritual values of sakinah, mawaddah, and rahmah. Collaboration between the pesantren and UIN SATU Tulungagung also resulted in a comprehensive premarital module that can be utilized as a sustainable program. This activity demonstrates that premarital counseling grounded in psychological, religious, and practical approaches is highly effective in preparing santri to face married life in a mature and responsible manner.